The Jesuits and globalization : historical legacies and contemporary challenges - Banchoff, Thomas F., 1964-; Casanova, José (Georgetown University Press, 2016)
The Society of Jesus, commonly known as the Jesuits, is the most successful and enduring global missionary enterprise in history. Founded by Ignatius Loyola in 1540, the Jesuit order has preached the Gospel, managed a vast educational network, and shaped the Catholic Church, society, and politics in all corners of the earth. The Jesuits' international impact and openness to dialogue with non-European cultures generated controversy--and led to their suppression by Pope Clement XIV in 1773. Restored in 1814, the Jesuits grew rapidly and had particular influence on the formation of schools and universities, an influence that continues to this day. In our global era marked by deep religious and cultural pluralism, what can we learn from the historical and contemporary experience of the Society of Jesus? What do the Jesuits tell us about globalization, and what can globalization tells us about the Jesuits? This volume is divided into two parts, historical legacies and contemporary challenges, and brings together leading scholars such as comparative theologian Francis Clooney, SJ, historian John O'Malley, SJ, Brazilian theologian Maria Clara Bingemer, and ethicist David Hollenbach, SJ, to focus on three critical themes: mission and dialogue; education and the human person; and justice and the common good.